The Effect of Time Pressure on the Quality of Fillings and Arousal Levels of Dentists - Kaisa M. Leinonen; Jukka Leinonen; Mohammed Al‐Haroni; Jan‐Are K. Johnsen (Clinical and Experimental Dental Research)
ABSTRACT Objectives We investigated the impact of time pressure on dentists' arousal levels and the immediate quality of composite resin fillings using two filling techniques in a simulated clinical setting. Material and Methods Forty‐two dentists and dental students were randomized to fill an identical Class II cavity either with the bulk‐fill base technique or the conventional incremental technique. The task was performed first under timing and then under time pressure. Arousal levels were investigated with a 100 mm visual analog scale (VAS) and a wireless wrist‐mounted triaxial accelerometer. The surface porosity and marginal gaps on the approximal surfaces of the fillings were evaluated using a stereomicroscope and specific probes according to the FDI criteria for restoration evaluation. Results Time pressure significantly increased arousal overall (F = 14.98, p < 0.05), and there was a significant effect of the experimental group on participants' arousal levels under time pressure (F = 7.78, p < 0.05); Dunn–Bonferroni tests indicated significantly lower arousal levels (p < 0.05) for the bulk‐fill base technique (M = 4.53, SD = 2.17) compared to the conventional incremental technique (M = 6.68, SD = 1.86). The bulk‐fill base technique showed superior quality under time pressure (X2 = 4.71, p = 0.030). Less experienced operators achieved better quality with the bulk‐fill base technique (Χ2 = 5.62, p = 0.018), while operator experience did not correlate with arousal levels under time pressure. Conclusions Employing the bulk‐fill base technique under time pressure led to reduced operator arousal levels and improved the immediate quality of fillings. Clinical Relevance The bulk‐fill base technique shows promise in being resistant to common work environment factors in dentistry, such as time pressure and stress, without compromising the quality of fillings. Utilizing innovative techniques, such as the bulk‐fill base technique, in a clinical setting can contribute to mitigating the operator's stress and enhancing the quality of care provided.